Genome-driven insights into Bacillus safensis strain B7 as a seed coating agent for plant growth promotion and alleviation of biotic and abiotic stresses. - Maissa Ben-Jabeur; Zayneb Kthiri; Salma Jallouli; Kalthoum Harbaoui; Zoubeir Chamekh; Sawsen Ayadi; Youssef Trifa; Walid Hamada (PLoS ONE)
Despite the significant increase in the use of plant growth-promoting bacteria (PGPB) in agriculture, there is a dearth of studies addressing the impact of seed coating with PGPB on plant productivity. The main objective of this research is to evaluate the potential of Bacillus safensis strain B7 as a seed coating agent to confer plant growth promotion and tolerance against biotic and abiotic stress. The whole-genome sequencing of strain B7 was also performed to study its genomic features. The effect of seed coating with strain B7 was assessed on seed water uptake, germination and seedling dry weight under controlled conditions. Besides, the direct and indirect effect against biotic stress was evaluated through antifungal activity and potential in stimulating the induced systemic resistance (ISR) under controlled conditions. Afterwards, the effect was evaluated in the field under drought stress conditions, based on the traits of grain yield (GY), straw yield, number of spikes/m2, and thousand kernel weight (TKW). It is noticeable that seed coating with strain B7 resulted in greater and faster water uptake. Germination and plant growth similarly boosted. Strain B7 was able to hamper the mycelial growth of F. culmorum and S. sclerotiorum and to induce ISR, after B. cinerea infection, in melon leaves taken from root-treated plants. In the field, seed coating with strain B7 improved wheat performance under the different environments and mitigated the effect of drought on spikes/m2, GY and TKW. The observed impact on wheat plants is supported by genomic analysis of strain B7 showing the presence of genes related to beneficial plant-bacteria interactions involved in plant colonization, growth promotion and alleviation of stress. Therefore, B. safensis strain B7 has promising applications in the seed treatment industry to increase plant yield and alleviate the impact of stress.